2017
DOI: 10.1017/s1751731116001683
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E is the major contributor to the antioxidant capacity in lambs fed whole dried citrus pulp

Abstract: The aim of this study was to investigate the effect of dietary whole dried citrus pulp (DCP) on the antioxidant status of lamb tissues. In total, 17 lambs were divided into two groups and fed for 56 days: a barley-based concentrate diet (CON -eight animals), or a concentrate-based diet including 35% DCP to partially replace barley (CIT -nine animals). The CIT diet contained a double concentration of phenolic compounds than the CON diet (7.9 v. 4.0 g/kg dry matter (DM), respectively), but had no effect ( P > 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 33 publications
1
23
1
1
Order By: Relevance
“…Citrus phenolic compounds, mainly flavonoids, possess antioxidant activity, and their intake with the diet has been suggested to increase the antioxidant capacity of animal tissue. However, the possible mechanisms for the antioxidant effects are not clear (Luciano et al, 2017). Indeed, Luciano et al (2017) reported that despite the fact that flavonoids are generally considered the main antioxidants in citrus fruits, α-tocopherol plays the major role in improving antioxidant capacity of muscle of lambs fed diets supplemented with DCP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Citrus phenolic compounds, mainly flavonoids, possess antioxidant activity, and their intake with the diet has been suggested to increase the antioxidant capacity of animal tissue. However, the possible mechanisms for the antioxidant effects are not clear (Luciano et al, 2017). Indeed, Luciano et al (2017) reported that despite the fact that flavonoids are generally considered the main antioxidants in citrus fruits, α-tocopherol plays the major role in improving antioxidant capacity of muscle of lambs fed diets supplemented with DCP.…”
Section: Discussionmentioning
confidence: 99%
“…The orange juice industry produces organic waste such as dried orange pellets that can be used for animal feeding as a source of dietary energy (Bampidis and Robinson, 2006). Furthermore, citrus pulp can be a source of residual bioactive molecules with antioxidant properties, including phenolic compounds (Santos et al, 2014;Luciano et al, 2017) and vitamin E (Luciano et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Supporting the previous hypothesis, the higher retinol content in the liver but lower concentration in the plasma of lambs on the sainfoin diet compared to those on the intensive diet was related to a time- and dose-dependent depletion of retinol caused by the concentrate fed during the fattening period before slaughter, as reported in steers [ 35 ]. Usually, the α-tocopherol content in the liver reflects differences due to the diet when this diet was fed until slaughter [ 14 , 36 ]. In the present study, the different α-tocopherol content in the maternal feedstuffs was not reflected in the liver of the lambs as has been reported previously in suckling lambs [ 10 ], probably due to the fattening period of 28 days when the lambs received only concentrate and straw with low α-tocopherol content.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have pointed out a great number of natural sources of vitamin E that may be used to supplement grain-based diets. Chesnutt, mimosa and tara extracts, dried tomato pomace, rosemary distillation residues, dried citrus pulp and olive cake are some feasible examples of alternative sources of vitamin E available in many regions where lambs grow intensively (Luciano et al, 2013;Luciano et al, 2017;Valenti et al, 2018a;Valenti et al, 2018b;Yagoubi et al, 2018). Moreover, these resources are cheaper and ecologically friendly, since they are agro-industrial by-products.…”
Section: Accepted Manuscriptmentioning
confidence: 99%